2009
DOI: 10.1021/ac802286a
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear Archeology in a Bottle: Evidence of Pre-Trinity U.S. Weapons Activities from a Waste Burial Site

Abstract: During World War II, the Hanford Site in Washington became the location for U.S. plutonium production. In 2004, a bottle containing a sample of plutonium was recovered from a Hanford waste trench. Here, state-of-the-art instrumental analyses, reactor model simulations, and investigative science techniques were used to provide insights as to the origin of this unknown sample, a process collectively termed as nuclear archeology. Isotopic age dating conducted on the sample in 2007 indicated the sample was separat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
31
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 19 publications
(22 reference statements)
0
31
0
Order By: Relevance
“…An analogous approach was used in an investigation of Manhattan Project-era plutonium discovered buried in a glass jug in a waste trench at the Hanford site in Washington State (Schwantes et al 2009). The jug contained hundreds of milligrams of Pu, and radiochronometry analyses were made, among other analyses, in the attempt to identify the origin and history of this material.…”
Section: Figurementioning
confidence: 99%
See 4 more Smart Citations
“…An analogous approach was used in an investigation of Manhattan Project-era plutonium discovered buried in a glass jug in a waste trench at the Hanford site in Washington State (Schwantes et al 2009). The jug contained hundreds of milligrams of Pu, and radiochronometry analyses were made, among other analyses, in the attempt to identify the origin and history of this material.…”
Section: Figurementioning
confidence: 99%
“…There are three potential sources for the U present in this sample: (a) U produced by radioactive decay of Pu, (b) U derived from irradiated reactor fuel that was not completely separated from Pu during reprocessing, and (c) natural U derived from the local environment. Historical records indicated that US plutonium production reactors operating at the time were using natural uranium fuel, and reactor modeling indicated that reactor operations would not have substantially modified the isotopic composition of the uranium fuel (Schwantes et al 2009). Therefore, any uranium present that was not produced by radioactive decay is expected to have a near-natural uranium isotopic composition.…”
Section: Figurementioning
confidence: 99%
See 3 more Smart Citations